Radiation effects of MHD Oscillatory Rotation Flow through a Porous Medium bounded by two Vertical Porous Plates in the Presence of Hall Current and Dufour effect with chemical reaction - K. Balamurugan; R. Karthikeyan (International Journal of Mathematics And its Applications, 2016)
In this Article, Radiation Effects of Oscillatory flow through a porous medium bounded by two vertical porous plates in the presence of Hall Current and Dufour Effect with homogeneous First order chemical reaction under the influence of uniform magnetic field is studied. One plate is kept stationary and another plate is oscillating with uniform velocity. The Plates are subjected to the constant injection and suction velocities respectively. The basic governing equations of the problem are transformed into a system of non dimensional differential equations, which are solved analytically by using Perturbation techniques. The dimensionless Velocity, temperature and concentration profiles are displayed graphically showing the effects of fluid flow for the different values of the parameters involving in this problem like Hartmann Number M, Radiation Parameter F, Grashof Number Gr, chemical reaction parameter R, Dufour effects Du, It is observed that increase of Permeability parameter K, Hall Parameter m, shows the increase effects of Velocity profile. The increase of chemical reaction parameter R shows decrease effects of concentration.